Sampling and statistics in assessment of fresh produce - Walsh, Kerry (Burleigh Dodds Series in Agricultural Science, 2022)
New measurement technologies are facilitating new approaches to the improvement of safety and quality in agri-food supply chains. However, measurement uncertainty and choice of sampling strategy can influence the outcomes of assessment programmes. This chapter provides a sampler of calculations of population statistics, required sample sizes and approaches to developing and implementing a sampling strategy. While examples from the fresh produce sector are given, the sampler is of relevance to both the student and the practitioner operating in agri-supply chains more generally.